46. MALARIA CONTROL AND ELIMINATION: ACHIEVEMENTS AND CHALLENGES IN PREVENTION OF RE-ESTABLISHMENT OF MALARIA IN CENTRAL VIETNAM (Vietnam Journal of Community Medicine, 2025)
Background: Malaria remains a significant public health concern, impacting both the well-being and economic stability of individuals residing in endemic areas. Objective: To assess the outcomes of malaria control and elimination efforts in Central Vietnam from 2020 to 2024. Methods: A retrospective descriptive analysis and an epidemiological evaluation of malaria. Results: Between 2020 and 2024, malaria cases and deaths declined; however, this reduction has not been sustained. By 2024, malaria cases had dropped by 79.66% compared to 2020, and the malaria parasite rate had fallen by 61.54%. Plasmodium falciparum remains the predominant parasite species, raising concerns over resistance to artemisinin and its derivatives, which complicates treatment efforts. Notably, Plasmodium malariae infections have surged, particularly in Khanh Hoa province. The resurgence of major malaria vectors, particularly Anopheles dirus, with potential insecticide resistance, coupled with factors such as population mobility (forest workers, outdoor sleepers, and cross-border travelers) and inefficiencies in local healthcare services, pose substantial challenges to malaria control and elimination programs. As of now, four out of 15 provinces/cities—Hue, Da Nang, Quang Ngai, and Binh Dinh—have achieved malaria elimination certification. Conclusion: The risk of malaria resurgence remains significant for communities in Central Vietnam. Targeted and effective strategies must
Keywords: malaria control and elimination